DEMURRAGE HANDLING OF FERTILIZER UNLOADING PROCESS AT PT. ZONA MANDIRI INDOTRANS PALU - Shendy, Shendy Amelya Mattalitti; Sulaeman Miru; Asngadi; Saharuddin Kaseng; Syamsuddin (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2023)
This study aims to determine and analyze the occurrence of demurrage at PT Zona Mandiri Indotrans,to determine and analyze the factors that cause demurrage at PT Zona Madiri Indotrans and to determine and analyze the efforts made by PT Zona Mandiri Indotrans in overcoming demurrage due to delays in loading and unloading fertilizers. This research was conducted at one of the freight forwarder companies in Palu City, PT Zona Mandiri Indotrans regarding fertilizer unloading activities that cause demurrage with a total of three informants. The approach used in this research is a qualitative approach and uses the NVivo 12 Plus software analysis tool. The results showed that demurrage occurred at PT Zona Mandiri Indotrans due to delays in fertilizer unloading activities. The factors causing demurrage are lack of truck fleet, truck fleet damage, lack of unloading labor, scarcity of diesel fuel, unloading tools, unfavorable weather and late B/L (Bill of Lading) documents. Efforts made by PT Zona Mandiri Indotrans in handling demurrage that occurs due to delays in loading and unloading fertilizers, the company rents a warehouse to store fertilizers that have not been loaded so that the containers used can be immediately returned to the shipping party and the company supplies diesel fuel for each truck fleet before the goods arrive at the port.